2010
DOI: 10.1128/aac.00661-10
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Molecular Characterization of Extensively Drug-Resistant Mycobacterium tuberculosis Clinical Isolates from the Delhi Region in India

Abstract: We screened 194 Mycobacterium tuberculosis strains isolated from tuberculosis (TB) patients in Delhi and neighboring regions in India to identify the prevalence of extensive drug resistance (XDR) in clinical isolates. Among these, 104 isolates were found to be multidrug resistant (MDR), and 6 were identified as XDR isolates, which was later confirmed by antimicrobial susceptibility testing against the respective drug screening panel. Genotyping was carried out by amplifying and sequencing the following genes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Screening of the rrs gene for detection of resistance to AMK, KAN, and CAP revealed the A1401G mutation to be the most common and present mutation in 66% of XDR isolates, consistent with reports from India and China (4,34,47). All isolates with an rrs nt 1401 mutation were KAN and AMK resistant, but 51.5% were CAP susceptible.…”
Section: Discussionsupporting
confidence: 62%
“…Screening of the rrs gene for detection of resistance to AMK, KAN, and CAP revealed the A1401G mutation to be the most common and present mutation in 66% of XDR isolates, consistent with reports from India and China (4,34,47). All isolates with an rrs nt 1401 mutation were KAN and AMK resistant, but 51.5% were CAP susceptible.…”
Section: Discussionsupporting
confidence: 62%
“…treated PTB patients60979.379.38.767.932.13.0MGIT 960Tertiary hospital18Sharma S K et al (c), 2011 [62]Delhi2008–2009Newly diagnosed PTB patients1771.71.11.1LJPrimary healthcare19Yadav R et al, 2013 [63]Chandigarh2008–2010Combined PTB patients17148.55.91.24.714.017.033.35.9LJTertiary hospital20Gupta A et al (a), 2011 [64]Varanasi2008–2010Combined PTB patients28857.635.8LJTertiary hospital21Sagar T et al, 2013 [65]Delhi2009–2010Combined PTB patients365.62.82.8LJTertiary hospital22Singh N et al, 2014 [66]Delhi2009–2012Prev. treated PTB patients35367.7167.71Not specifiedRNTCP district centers23Khanna A et al, 2010 [67]Delhi2010Combined PTB patients19453.63.1MGIT 960Referral cases from diagnostic center24Maurya A K et al, 2013 [45]Lucknow2011–2012<...>…”
Section: Resultsmentioning
confidence: 99%
“…Several studies including our group have reported incidences of Rifampin resistant Mycobacterium in clinical isolates. (32)(33)(34)(35) Interestingly, the 96 % of the Mycobacterium tuberculosis clinical isolates screened were found to have in 81 bp core region of rpoB gene, which encodes for the beta subunit of RNA polymerase. (36) Missense mutations in codons 513, 526, or 531 resulted in high level Rifampin resistance; whereas amino acid changes at position 514 or 533 usually resulted in low levels of Rifampin resistance.…”
Section: Understanding the Molecular Basis Of Drugresistance In Tb Dmentioning
confidence: 99%